Magnetic, thermal and spectral characterization of 2,6-dimethoxybenzoates of Co(II), Ni(II) and Cu(II) - Ferenc, Wieslawa; Walków-Dziewulska, Agnieszka; Sarzyński, Jan (Eclética Química, 2006)
The complexes of 2,6-dimethoxybenzoic acid anion with ions of Co(II), Ni(II), and Cu(II) have been synthesized as polycrystalline solids, and characterized by elemental analysis, spectroscopy, magnetic studies, and also by X-ray diffraction and thermogravimetric measurements. The analysed complexes have following colours: pink for Co(II), green for Ni(II), and blue for Cu(II) compounds. The carboxylate group binds as monodentate, and bidentate bridging and chelating ligands. On heat- ing in air to 1173 K the complexes decompose in four, three or two steps. At first, they dehydrate in one or two steps to anhydrous salts, that next decompose to oxides of the respective metals. The solu- bility of the investigated dimethoxybenzoates in water at 293 K is of the order of 10 -2 mol/dm 3 . Their magnetic moments were determined in the temperature range of 76-303 K. The results reveal the com- pounds of Co(II) and Ni(II) to be high-spin complexes and that of Cu(II) to form dimer.